2019
DOI: 10.1371/journal.pntd.0007401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of host cell binding specificity mediated by the Tp0136 adhesin of the syphilis agent Treponema pallidum subsp. pallidum

Abstract: Background Syphilis affects approximately 11 million people each year globally, and is the third most prevalent sexually transmitted bacterial infection in the United States. Inability to independently culture and genetically manipulate Treponema pallidum subsp. pallidum , the causative agent of this disease, has hindered our understanding of the molecular mechanisms of syphilis pathogenesis. Here, we used the non-infectious and poorly adherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…GAGs are integral components of ECM of mammalian cells. Previous studies have shown the ability of T. pallidum adhesins to bind to proteoglycans, fibronectin, and laminin (Brinkman et al, 2008;Kao et al, 2017;Djokic et al, 2019). We show here that unlike VAR2CSA, Tp0954-expressing bacteria bind significantly to purified, immobilized dermatan sulfate and heparin (Figure 3).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…GAGs are integral components of ECM of mammalian cells. Previous studies have shown the ability of T. pallidum adhesins to bind to proteoglycans, fibronectin, and laminin (Brinkman et al, 2008;Kao et al, 2017;Djokic et al, 2019). We show here that unlike VAR2CSA, Tp0954-expressing bacteria bind significantly to purified, immobilized dermatan sulfate and heparin (Figure 3).…”
Section: Discussionsupporting
confidence: 50%
“…Recently, we developed an effective approach of using heterologous expression system involving a closely related spirochetal species, B. burgdorferi to study T. pallidum infection. This has led us to make several important discoveries elucidating the mechanisms that facilitate attachment to host components of this obligate extracellular pathogen (Chan et al, 2016;Djokic et al, 2019;Parveen et al, 2019). In this study, we conducted functional analysis of the T. pallidum adhesin Tp0954.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAGs are integral components of ECM of mammalian cells. Previous studies have shown the ability of T. pallidum adhesins to bind to proteoglycans, fibronectin, and laminin (Brinkman et al, 2008 ; Kao et al, 2017 ; Djokic et al, 2019 ). We show here that unlike VAR2CSA, Tp0954-expressing bacteria bind significantly to purified, immobilized dermatan sulfate and heparin ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used the non-infectious, poorly adherent B. burgdorferi strain B314 (Sadziene et al, 1993 ) in our studies to express and study the function of T . pallidum putative surface proteins and evaluate their potential as vaccine candidates (Chan et al, 2016 ; Djokic et al, 2019 ; Parveen et al, 2019 ). There are no cases of congenital Lyme disease reported until now.…”
Section: Introductionmentioning
confidence: 99%